Profile and mental health characterization of childhood overprotection/overcontrol experiences among Chinese university students: a nationwide survey - Zhang, Jiamei; Wu, Zhipeng; Tao, Haojuan; Chen, Min; Yu, Miaoyu; Zhou, Liang; Sun, Meng; Lv, Dongsheng; Cui, Guangcheng; Yi, Qizhong; Tang, Hong; An, Cuixia; et al. (Frontiers in Psychiatry, 2023)
The childhood experiences of being overprotected and overcontrolled by family members have been suggested to be potentially traumatic. However, the possible associated factors of these experiences among young people are still not well studied. This study aimed to partly fill such gaps by a relatively large, nationwide survey of Chinese university students. A total of 5,823 university students across nine different provinces in China were included in the data analyses. All participants completed the overprotection/overcontrol (OP/OC) subscale in a recently developed 33-item Childhood Trauma Questionnaire (CTQ-33). Data were also collected on all participants’ sociodemographic profiles and characterization of mental health. Binary logistic regression was conducted to investigate the associated sociodemographic and psychological factors of OP/OC. The prevalence of childhood OP/OC was estimated as 15.63% (910/5,823) based on a cutoff of OP/OC subscale score ≥ 13. Binary logistic regression suggested that being male, being a single child, having depression, having psychotic-like experiences, lower family functioning, and lower psychological resilience were independently associated with childhood OP/OC experiences (all corrected-p＜0.05). The OP/OC was also positively associated with all the other trauma subtypes (abuses and neglects) in the CTQ-33, while there are both shared and unique associated factors between the OP/OC and other trauma subtypes. Post-hoc analyses suggested that OP/OC experiences were associated with depression in only females, and associated with anxiety in only males. Our results may provide initial evidence that childhood OP/OC experiences would have negative effects on young people's mental health which merits further investigations, especially in clinical populations.